Peningkatan Kemampuan Komunikasi Matematis Melalui Model Problem Based Learning (PBL) Pada Siswa Kelas VIII MTs N 1 Rokan Hulu - Ermida; Arcat; Afri, Lusi Eka (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to determine the improvement of mathematical communication skills through the Problem-Based Learning (PBL) model in eighth-grade students of MTs N 1 Rokan Hulu. This type of research is a Quasi Experiment with the Nonequivalent Pretest Posttest Control Group Design research design. The population in this study was eighth-grade students of MTs N 1 Rokan Hulu. Random sampling was done, resulting in class VIIID as the experimental group and class VIIIC as the control group. The experimental group applied the Problem-Based Learning (PBL) model, while the control group applied conventional learning. Hypothesis testing used the Mann-Whitney test because the data were not normally distributed. The calculation results obtained a z-score of 2.61 and a z-table value of 1.96 with a significance level of Î± = 0.05. Since the calculated z-score > the critical value from the table, H0 was rejected. Thus, it can be concluded that there is an improvement in mathematical communication skills through the Problem-Based Learning (PBL) model in eighth-grade students of MTs N 1 Rokan Hulu.